(untitled) (Journal of Economic Research & Business Administration, 2015)
The economic crisis has strengthened requirement for auditor’s services. At this time requirements to check auditor’s quality and its compulsion sharply become tougher, the market requirement for audit services increases. Internal audit is necessary for prevention of resources loss and realization of necessary changes in the enterprise.